Program Innovation in the National Amil Zakat Management System: A Step Towards Enhancing the Welfare of Mustahik - Rozi, Muhammad Fakrur; Mashudi; Qomarul Huda (Perisai : Islamic Banking and Finance Journal, 2024)
The continued development of the ZIS management system which gave birth to new programs which are the result of the program innovations of each amil zakat institution is expected to be able to improve the welfare of mustahik in various fields. This study aims to find out the collection, distribution, utilization and reporting of zakat, infaq, alms (ZIS) funds at BAZNAS Tulungagung and NU Care-LAZISNU Tulungagung. This research method is qualitative with descriptive research type, data collection techniques with in-depth interviews, moderate participation observation and documentation, data analysis model of Miles and Huberman. Checking the validity of the data by extending observations, increasing persistence, triangulation and member checks. The results of this study are 1) collection at BAZNAS Tulungagung through UPZ, Bank Transfers, Counters/counters, by conducting outreach to agencies and social media Instagram Facebook and YouTube while NU Care- LAZISNU Tulungagung through the MWC, Twigs and congregation, bank transfers, zakat car, with socialization to congregations, and social media Instagram Facebook and WhatsApp groups. 2) Distribution of BAZNAS Tulungagung through education compensation programs, medicine for Islamic boarding schools, mass circumcision, house renovations, and Zakat Community Development (ZCD) for tourist villages while NU Care- LAZISNU Tulungagung through education care programs, free medical treatment, disaster response, mosque construction, programs wholesale. 3) Utilization of BAZNAS Tulungagung through a basic food distribution program for orphans totaling 1500 pcs each year, One Family One Bachelor scholarship (SKSS) at 4 universities in Tulungagung for underprivileged families, "fertile goat" farms of 50 goats in the area village of Besole, business capital for etek traders is 1 million rupiah, while NU Care-LAZISNU Tulungagung through the staple rice program for the poor, 550 free eyeglasses for mustahik in the education sector, 140 "integrated goat" farms in the village area pakisaji, business capital for small businesses or wholesalers of 2 million rupiah. 4) BAZNAS Tulungagung reporting through the BAZNAS Information Management System (SIMBA) and Instagram social media and the official website while NU Care-LAZISNU Tulungagung submits reports to BAZNAS Tulungagung, People's Welfare, Ministry of Religion and social media Instagram and Facebook and WhatsApp groups.